Effects of an iPad-based Speech-Generating Device Infused into Instruction with the Picture Exchange Communication System for Adolescents and Young Adults with Severe Autism Spectrum Disorder. Issue 6 (November 2019) - Wendt, Oliver; Hsu, Ning; Simon, Kara; Dienhart, Alyssa; Cain, Lauren
This study used a multiple baseline, single-subject research design to investigate the efficacy of an iPad ® -based speech-generating device (SGD). The iPad was equipped with the SPEAKall! ® application to function as a SGD. SGDs are a form of aided augmentative and alternative communication (AAC) allowing a user to communicate using digitized and/or synthesized speech. Instruction followed a modified version of the intervention phases from the Picture Exchange Communication System (PECS). This modified PECS protocol was implemented with two adolescents and one young adult between the ages of 14 and 23. All three participants were diagnosed with severe autism spectrum disorder and little to no functional speech. Dependent measures included the ability to request for edible and tangible items as the primary measure, and the ability to engage in natural speech production as an ancillary measure to determine simultaneous, additive effects on speech acquisition. Results indicated increases in requesting behaviors for all three participants across intervention and maintenance phases. Once participants mastered requesting of edible items, they were able to generalize the skill to tangible items. However, mixed results were found when targeting natural speech production. Based on the current findings, the infusion of an iPad-based SGD into PECS instruction may be effective in increasing initial requesting skills; however, a facilitative effect on increasing speech acquisition cannot necessarily be expected for every participant.